2022
DOI: 10.3390/molecules27051595
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Therapeutic Perspectives of Phytosterols in Insulin Resistance: A Mechanistic Approach

Abstract: Natural products in the form of functional foods have become increasingly popular due to their protective effects against life-threatening diseases, low risk of adverse effects, affordability, and accessibility. Plant components such as phytosterol, in particular, have drawn a lot of press recently due to a link between their consumption and a modest incidence of global problems, such as Type 2 Diabetes mellitus (T2DM), cancer, and cardiovascular disease. In the management of diet-related metabolic diseases, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…ese results agree with our previous findings that β-sitosterol has a strong influence on the regulation of hyperglycemia. In accordance with the present findings, we have recently reviewed the potential role of phytosterols particularly β-sitosterol and its perspectives on the translocation of GLUT4 containing vesicles on the PM, which is crucial for the glucose uptake and oxidation in insulin-sensitive tissues such as skeletal muscle, adipose tissue, and in reducing the diabetes risk and/or insulin resistance [69]. Our current research, being the rst of its kind, has attempted to prove the mechanisms by which β-sitosterol (a potent phytosterol) is involved in the regulation of glucose absorption and translocation of signaling molecules involved in the GLUT4 containing vesicle fusion on the PM in HFD and sucroseinduced T2DM (Figure 12).…”
Section: Discussionsupporting
confidence: 87%
“…ese results agree with our previous findings that β-sitosterol has a strong influence on the regulation of hyperglycemia. In accordance with the present findings, we have recently reviewed the potential role of phytosterols particularly β-sitosterol and its perspectives on the translocation of GLUT4 containing vesicles on the PM, which is crucial for the glucose uptake and oxidation in insulin-sensitive tissues such as skeletal muscle, adipose tissue, and in reducing the diabetes risk and/or insulin resistance [69]. Our current research, being the rst of its kind, has attempted to prove the mechanisms by which β-sitosterol (a potent phytosterol) is involved in the regulation of glucose absorption and translocation of signaling molecules involved in the GLUT4 containing vesicle fusion on the PM in HFD and sucroseinduced T2DM (Figure 12).…”
Section: Discussionsupporting
confidence: 87%
“…The total population with diabetes is predicted to reach 643 million by 2030 and 783 million by 2045. Diabetes-related disasters 6.7 million fatalities and at least 966 billion USD in medical costs [ 7 ]. Ethiopia has 800,000 diabetes patients in 2000, and the figure is predicted to rise to 1.8 million by 2030 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of clinical trials found that phytosterols reduce insulin resistance, but not enough to generate clinically significant improvements in glucose metabolism [ 273 ]. This is backed by in vitro studies that demonstrated increased expression levels and activation of different components of the insulin receptor signaling pathway by phytosterols [ 274 , 275 ]. Cardiovascular risk.…”
Section: Resultsmentioning
confidence: 99%